PENGARUH TINGKAT IRADIASI TERHADAP SIFAT FISIS DAN MEKANIS KAYU KARET YANG DIIMPREGNASI DENGAN POLIESTER STIREN - Bakir Ginoga; B Sipayung S; Karnasudirdja Karnasudirdja; Suyitno Suyitno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
The effect of irradiation level i.e. two megarad (20 KGy), four megarad (40 KGy) and six megarad (60 KGy) pre impregnated with polyester styrene was investigated on rubber wood (Hevea brasiliensis Muell. Arg.). The samples were obtained from locally cultivated rubber trees at Jasinga subdistrict, Bogor, West Java. The treated wood properties tested include airdry density, hardness, compression parallel to the grain, compression perpendicular to the grain and impact bending strength, using the method described in ASTM D 143-52 (Anom., 1976). The swelling and shrinkage test specimen was 5.0 cm x 5.0 cm x 1.5 cm block and of 5.0 cm x 5.0 cm x 3.5 cm for water absorption determination.The test results revealed that irradiation treatment were highly significantly increase density, hardness, compression parallel to the grain and compression perpendicular to the grain, but decrease swelling, shrinkage and water absorption. Meanwhile, shrinkage and swelling on radial direction, and impact bending strength showed non-significant difference (P ≥ 0.05).It is also concluded that irradiation of two megarad (20 KGy) increase the density, hardness, compression parallel to the grainand compression perpendicular to the grain by one and half fold compared to untreated specimens. On the other hand, water absorption, swelling and shrinkage for tangential direction decrease to about the same magnitude when treated with the same level of irradiation compared to untreated ones.Impact bending strength showed non-significant difference for all treatment levels.